2006
DOI: 10.1111/j.1538-7836.2006.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of sequential maternal anti‐HPA‐1a antibody concentrations for the severity of fetal alloimmune thrombocytopenia

Abstract: To cite this article: Bertrand G, Martageix C, Jallu V, Vitry F, Kaplan C. Predictive value of sequential maternal anti-HPA-1a antibody concentrations for the severity of fetal alloimmune thrombocytopenia. J Thromb Haemost 2006; 4: 628-37.Summary. Background: Fetal/neonatal alloimmune thrombocytopenia results from maternal immunization against fetal platelet alloantigens (HPAs), and the major risk is intracranial hemorrhage. The severity of thrombocytopenia increases in subsequent pregnancies, and antenatal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 23 publications
3
69
1
1
Order By: Relevance
“…[4][5][6][7][8][9] Results from the present work, including 161 non-compatible pregnancies, further substantiate this relationship. The theoretically best antibody cut-off level for predicting an outcome appraises sensitivity and specificity equally, but is not necessarily the optimal level for use in clinical practice since the consequences of false-negative and false-positive results may be very different.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…[4][5][6][7][8][9] Results from the present work, including 161 non-compatible pregnancies, further substantiate this relationship. The theoretically best antibody cut-off level for predicting an outcome appraises sensitivity and specificity equally, but is not necessarily the optimal level for use in clinical practice since the consequences of false-negative and false-positive results may be very different.…”
Section: Discussionsupporting
confidence: 68%
“…27 We and others have previously reported that anti-HPA 1a antibody levels decrease throughout pregnancy in women who have had a previous pregnancy. 9,[28][29][30] The fact that the levels of antibodies to the rubella antigen were stable during pregnancy disproves the hypothesis that the decrease in anti-HPA 1a antibody levels could be due to the normal hemodilution that occurs during pregnancy. Furthermore, women with anti-HPA 1a antibodies and an HPA 1a negative fetus did not experience decreasing anti-HPA 1a levels during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunization against HPA-1a occurs in ;1:450 random pregnancies. [8][9][10] Although platelet decrement is related to antibody titer in FNAIT, 8,11,12 this correlation is not strict, as cases with low titers and very low platelet counts, as well as cases with high titers and normal platelet counts, are frequently observed. Recently we found that at least some of this discrepancy is due to differences in the functional quality of these antibodies, determined by its Fc glycosylation, in particular the level of core fucosylation.…”
Section: Introductionmentioning
confidence: 99%